EFFECTS OF IRON DEFICIENCY ANEMIA IN SURGICAL SITE INFECTION - Zulfiqar, Muhammad Umair; Ghani, Umer Fayyaz; Mallhi, Ayub Ashraf; Mahmood, Khalid; Iqbal, Maria; Ans, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine effect of iron deficiency anemia on the patients developing surgical site infection at surgical department of a tertiary care setup in Pakistan.Study Design: Comparative prospective study.Place and Duration of Study: Department of Surgery, Pak Emirates Military Hospital Rawalpindi, from Nov 2018 to Mar 2019.Methodology: A total of 152 indoor hospitalized patients were included in the study. Surgical site infection was assessed by a consultant surgeon according to definitions provided by the Centers for Disease Control and Prevention (CDC) National nosocomial infections surveillance system. Iron deficiency anemia was classed on the basis of hemoglobin and ferritin levels.Results: Eighty six (56.6%) patients were male while 66 (43.4%) patients included in the study were female. Commonest surgical procedure was laparotomy 29 (19.1%) followed by the hernioplasty 27 (17.7%). Out of 152 patients undergoing surgery & admitted in ward, 35 (23.1%) showed the presence of surgical site infection while 117 (76.9%) had no infection. Seventy eight (51.3%) patients had iron deficiency anemia while 74 (48.7%) patients were not anemic. History of transfusion during the surgery and presence of iron deficiency anemia was significantly associated with surgical site infection in the target population.Conclusion: Study exhibited high frequency of surgical site infection in the target population. Regular screening for anemia should be performed at surgery department and patients with history of transfusion during the surgery should be looked after especially. Iron deficiency anemia emerged as an independent factor associated with presence of surgical site infection among surgical patients.